Negative affect and binge eating: Assessing the unique trajectories of negative affect before and after binge‐eating episodes across eating disorder diagnostic classifications. Issue 2 (8th December 2021) - Wonderlich, Joseph A.; Crosby, Ross D.; Engel, Scott G.; Crow, Scott J.; Peterson, Carol B.; Le Grange, Daniel; Wonderlich, Stephen A.; Fischer, Sarah
Abstract: Objective: Ecological momentary assessment (EMA) studies suggest that among individuals who binge eat, emotional states and binge eating are functionally related. However, it is unclear whether the trajectory of negative affect (NA) is the same across diagnostic groups or if specific changes in affect are unique to each diagnostic category. This study examined the moderating effect of diagnosis on the trajectory of negative affect before and after binge eating. Method: Adults with eating disorder diagnoses (anorexia nervosa [AN] = 118, bulimia nervosa [BN] = 133, binge‐eating disorder [BED] = 112) completed an EMA where they reported binge eating and negative affect throughout the day. Generalized estimating equation analyses were used to model the trajectories of NA before and after binge eating. Results: For all individuals, the linear trajectory of NA significantly increased before (B = 0.044, p < .001) and decreased following the binge‐eating episode (B = −0.054, p < .001). However, diagnosis moderated this trajectory. Specifically, individuals with BN had a greater change in linear trajectories of NA before (B = 2.305, p < .001) and after (B = −4.149, p < .001) binge eating compared to those with BED, but not those with AN. There were no differences in the trajectory of NA between individuals with BED or AN. Discussion: These findings suggest that binge‐eating episodes in BN may be more strongly associated with NA than in BED, but similar to binge‐eating episodes in AN.